The ICP-MS validated for measuring arsenic levels in muscle tissues of freshwater fishes in Ho Chi Minh City - Thang, Nguyen Quoc (Vietnam Journal of Chemistry, 2016)
The present study was carried out to investigate contamination of arsenic in 10 freshwater fish species (Oreochromis sp, Ophiocephalus maculatus, Anabas testudineus, Oreochromis niloticus, Trichogaster pectoralis, Clarias macrocephalus, Pangasius hypophthalmus, Pangasius bocourti, Cyprinus carpio, Macrognathus siamensis) that are most commonly consumed by the habitant of Ho Chi Minh City. The arsenic concentration in fish muscle was analyzed using ICP-MS. Linearity was evaluated by repeated three times using different concentrations in the range from 0.5 to 20 g/L with a determination coefficient (r2) of 0.9998. The limit of detection (LOD) and limit of quantification (LOQ) of the method were found to be 0.076 g/L and 0.253 g/L, respectively. Intra-assay precision levels were between 0.41 and 2.69  %. Inter-assay precision levels were between 2.11 and 4.17 %. Recovery of arsenic from fish muscle was found to be from 105 to 114 %. The resulted showed that the mean arsenic concentration in muscle of fish ranged from 0.38±0.06 to 6.28±0.20 ng/g. The overall results indicated that arsenic concentrations in fish muscle were lower than the permitted level set by Ministry of Health Vietnam and Food and Drug agent. Therefore, the consumption of the fish species might not pose a risk of arsenic toxicity. Keywords. Fish, Arsenic, ICP-MS.